Geologia e geoquímica do Granito Itaoca - Zenero, Jonas Menezes [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The Itaoca Granite is an intrusive circular batholite of 200 km2, located between the state of São Paulo and Paraná. It has a calcium alcaline composition, and its approximate age of 623 million years, has its genesis associated with the neoproterozoic evolution of the Mantiqueira Central Province. Its nesting rocks make up the Açungui Supergroup and present in the environments of the batholith with mineralogy typical of contact metamorphism. Thus facilitating the identification of the granitoid with the use of remote sensing images. Using textural, structural, staining and compositional aspects of the rock the massive was divided into three units and subdivided into 6 facies. They are the units Itaoca, Ribeira and an association of undifferentiated facies. Petrographically their rocks constitute basically hornblende-biotite-quartz monzonites to holo- to leucocratic monzogranites. They have porphyritic, unequigranular texture, medium to coarse granulation, isotropic to suboriented. The unit Itaoca constituted of rocks less evolved (quartz monzonites), possibly because it is a primary magmatic pulse in front of the unit ribeira. Geochemically, the granitoid is a peraluminous granite, type I cordilherian, syn to late collisional that intruded in a magmatic arc by the fusion of the inferior crust. Occurring during the Brazilian collision event, more specifically in the Apiaí orogen, between the initial, thrust falt, and final stages, of shearing. The deformations generated by the shear zones, referring to the lateral escape efforts, produced the milonitic to metagranitic rocks. They occur in the margins of the granite body, closer to the shear zones, and due to the difficulty of determining the facies belonging, make up the unit of associations of undifferentiated facies

O Granito Itaoca constitui um batólito intrusivo de forma circular, de 200 Km2, localizado entre o estado de São Paulo e Paraná. Possui composição cálcio alcalina, e idade aproximada de 623 milhões de anos, com gênese associada a evolução neoproterozoica da Província Mantiqueira Central. Suas rochas encaixantes compõem o Supergrupo Açungui e apresentam nos entornos do batólito mineralogia típica de metamorfismo de contato. Facilitando assim, a identificação do granitóide com o uso de imagens de sensores remotos. Utilizando de aspectos texturais, estruturais, coloração e composicionais da rocha o maciço foi dividido ainda em três unidades e subdividido em 6 fácies. São as unidades Itaoca, Ribeira e uma associação de fácies indiferenciadas. Petrograficamente suas rochas constituem basicamente hornblenda-biotita-quartzo monzonitos a monzogranitos, holo- a leucocráticos. Possuem textura porfirítica, inequigranular, granulação média a grossa, isotrópica a suborientada. Sendo a unidade Itaoca constituída de rochas menos evoluídas (quartzo monzonitos), possivelmente por se tratar de um pulso magmático primário frente a unidade ribeira. Geoquimicamente, o granitoide trata-se de um granito peraluminoso, tipo I cordilheriano, sin a tardi colisional que intrudiu em um arco magmático pela fusão da crosta inferior. Ocorrendo durante o evento de colisão brasiliana, mais especificamente no orógeno Apiaí, entre os estágios iniciais de cavalgamento, e finais, de cisalhamento. As deformações geradas pelas zonas de cisalhamento, referentes aos esforços de escape lateral, produziram as rochas miloníticas a metagraníticas. Elas ocorrem nas margens do corpo granítico, próximas das zonas cisalhantes, e devido à dificuldade de determinar a fácies pertencente, compõem a unidade de associações de fácies indiferenciadas
Keywords: Granito; Geologia; Geoquímica; São Paulo (Estado); Parana